Hydrogen production via CO2-CH4 reforming over cobalt-supported mesoporous alumina: A kinetic evaluation - Mahadi, Bahari; Herma Dina, Setiabudi; Trinh, Duy Nguyen; Aishah, Abdul Jalil; Nurul Aini, Razali; Vo, Dai-Viet N. (Elsevier Ltd, 2021)
The performance of cobalt supported on mesoporous alumina (MA) under the influence of reaction temperature (923 K–1073 K) and reactant partial pressure (10 kPa–40 kPa) for CO2–CH4 reforming was executed by using a tubular fixed-bed reactor. 10%Co/MA exhibited great catalytic performance (, and), credited to the well dispersion of Co within pore MA, strong metal-support interaction, and MA confinement ability. Based on Langmuir-Hinshelwood kinetic analysis, the dissociative adsorption of both reactants on a single Co active site was selected for this study. The lower value of activation energy (28.9 kJ mol−1) suggested that Co particles were finely scattered on the MA surface. Regardless of carbon types, the amount of coke accumulated on the spent 10%Co/MA within 8 h of CO2–CH4 reforming was inhibited due to fine Co distribution inside MA structure, as well as lessened with the raise of reforming temperature from 923 to 1073 K due to improvement in reverse Boudouard reaction.